Centro Social Marista Irmão Lourenço - serviço de apoio socioeducativo: uma experiência de educação não formal na área socioassistencial -SP - 2010 - Sousa, Joelma Aparecida de Freitas (2011)
The present dissertation is the result of a study performed in São Paulo at the Marista Ir. Lourenço Social Centre, aiming the SocioEducative support service as an experience of a non-formal education in the social assistential area. It focus on studying and analyzing this experience from the citizenship construction perspective of children and teenagers as owners rights. Conceptual references to the Non-Formal Education, Social Assistance and Citizenship, were taken for this research, based on contemporary authors of Social Service, Education and Sociology areas. It defined as hypothesis that the Non-Formal experience in the social assistential area developed at the Marista Ir. Lourenço Social Centre, has contributed significantly to learning, to children and teenagers socialization, and to the process of citizenship construction. Methodologically, this is a qualitative nature research, embodying bibliographic documental studies, field research and participating observation. A semi-structured interview with six integrants of the research was done: four teachers, the coordinator and the pedagogical assistant. The results confirmed the hypothesis, when contributing to the construction of the children and teenagers citizenship significantly, expressing a path in construction and reconstruction